Pharmacokinetics and Safety of 3 Months of Weekly Rifapentine and Isoniazid for Tuberculosis Prevention in Pregnant Women. (29th July 2021) - Mathad, Jyoti S; Savic, Rada; Britto, Paula; Jayachandran, Priya; Wiesner, Lubbe; Montepiedra, Grace; Norman, Jennifer; Zhang, Nan; Townley, Ellen; Chakhtoura, Nahida; Bradford, Sarah; Patil, Sandesh; et al.
Abstract: Background: Pregnancy increases the risk of tuberculosis and its complications. A 3-month regimen of weekly isoniazid and rifapentine (3HP) is safe and effective for tuberculosis prevention in adults and children, including those with HIV, but 3HP has not been evaluated in pregnancy. Methods: IMPAACT 2001 was a phase I/II trial evaluating the pharmacokinetics and safety of 3HP among pregnant women with indications for tuberculosis preventative therapy in Haiti, Kenya, Malawi, Thailand, and Zimbabwe (NCT02651259). Isoniazid and rifapentine were provided at standard doses (900 mg/week). Pharmacokinetic sampling was performed with the first (second/third trimester) and twelfth (third trimester/postpartum) doses. Nonlinear mixed-effects models were used to estimate drug population pharmacokinetics. Results: Of 50 participants, 20 had HIV and were taking efavirenz-based antiretroviral therapy. Among women without HIV, clearance of rifapentine was 28% lower during pregnancy than postpartum (1.20 vs 1.53 L/hour, P < .001), with area under the concentration-time curve (AUCSS ) of 786 and 673 mg × hour/L, respectively. In pregnant women with HIV, clearance was 30% higher than women without HIV ( P < .001), resulting in lower AUCss (522 mg × hour/L); clearance did not change significantly between pregnancy and postpartum. Pregnancy did not impact isoniazid pharmacokinetics. There were no drug-related serious adverse events, treatment discontinuations, or tuberculosis cases in women or infants. Conclusions: 3HP does not require dose adjustment in pregnancy. Rifapentine clearance is higher among women with HIV, but all women achieved exposures of rifapentine and isoniazid associated with successful tuberculosis prevention. The data support proceeding with larger safety-focused studies of 3HP in pregnancy. Clinical Trials Registration: ClinicalTrials.gov, NCT02651259. Abstract : The regimen of weekly isoniazid and rifapentine for 3 months for tuberculosis prevention was well tolerated in pregnant women, and target concentrations of both drugs were achieved at standard doses among women with and without human immunodeficiency virus.